Is objective and accurate cognitive assessment across the menstrual cycle possible? A feasibility study. (8th January 2015) - Farrar, Diane; Neill, Jo; Scally, Andy; Tuffnell, Derek; Marshall, Kay
Objectives: Variation in plasma hormone levels influences the neurobiology of brain regions involved in cognition and emotion processing. Fluctuations in hormone levels across the menstrual cycle could therefore alter cognitive performance and wellbeing; reports have provided conflicting results, however. The aim of this study was to assess whether objective assessment of cognitive performance and self-reported wellbeing during the follicular and luteal phases of the menstrual cycle is feasible and investigate the possible reasons for variation in effects previously reported. Methods: The Cambridge Neuropsychological Test Automated Battery and Edinburgh Postnatal Depression Scale were used to assess the cognitive performance and wellbeing of 12 women. Data were analysed by self-reported and hormone-estimated phases of the menstrual cycle. Results: Recruitment to the study and assessment of cognition and wellbeing was without issue. Plasma hormone and peptide estimation showed substantial individual variation and suggests inaccuracy in self-reported menstrual phase estimation. Conclusion: Objective assessment of cognitive performance and self-assessed wellbeing across the menstrual cycle is feasible. Grouping data by hormonal profile rather by self-reported phase estimation may influence phase-mediated results. Future studies should use plasma hormone and peptide profiles to estimate cycle phase and group data for analyses.